Tensiomyography Derived Parameters Reflect Skeletal Muscle Architectural Adaptations Following 6-Weeks of Lower Body Resistance Training - Wilson, Matthew T.; Ryan, Andrew M. F.; Vallance, Scott R.; Dias-Dougan, Alastair; Dugdale, James H.; Hunter, Angus M.; Hamilton, D. Lee; Macgregor, Lewis J. (Frontiers in Physiology, 2019)
The measurement of muscle-specific contractile properties in response to resistance training (RT) can provide coaches and practitioners valuable information regarding the physiological state of their athletes. Field based measurements of such contractile properties within specific muscle groups, could be beneficial when monitoring the efficacy of training or rehabilitation interventions. Thus, the aims of this study were; (i) to investigate the potential use of Tensiomyography (TMG) to quantify training adaptations and differences, in response to exercise specific lower limb RT; and (ii) investigate any associations between TMG parameters and accompanying muscle architectural measures. Non-resistance trained male participants (n=33) were randomly assigned to 1 of 3 single-exercise intervention groups (n=11 per group); back squat (BS), deadlift (DL), or hip thrust (HT). Participants completed a 6-week linearized training programme (2x per week), where the assigned exercise was the sole method of lower body training. Pre- and post-intervention testing of maximal dynamic strength was assessed by one repetition maximum (1RM) of BS, DL and HT. Additionally muscle architecture (pennation angle and muscle thickness) and muscle contractile properties of rectus femoris (RF) and vastus lateralis (VL) were obtained pre- and post-intervention. All three groups displayed significant increases all 1RM strength tests (p < 0.001; pη2 = 0.677-0.753). Strength increases were accompanied by significant overall increases in RF muscle thickness (p <0.001, pη2 =0.969), and pennation angle (p = 0.007, pη2 = 0.220). Additionally, an overall reduction in RF radial muscle belly displacement (Dm) (p < 0.001, pη2 =0.427) was observed. Significant negative relationships were observed between RF Dm and pennation angle (p = 0.003, r = -0.36), and with RF Dm and muscle thickness (p < 0.001, r = -0.50). These findings indicate that TMG is able to detect improved contractile properties, alongside improvements in muscle function within an untrained population. Furthermore, the observed associations between Dm and muscle architecture suggest that TMG contractile property assessments may be used to obtain information on muscle geometry.